Epstein–Barr Virus Epithelial Cancers—A Comprehensive Understanding to Drive Novel Therapies - Han, Shuting; Tay, Joshua K.; Loh, Celestine Jia Ling; Chu, Axel Jun Ming; Yeong, Joe Poh Sheng; Lim, Chwee Ming; Toh, Han Chong (Frontiers in Immunology, 2021)
Epstein-Barr virus (EBV) is a ubiquitous oncovirus associated with multiple epithelial and lymphoid cancers. Among the epithelial cancers, nasopharyngeal carcinoma (NPC), lymphoepithelioma-like carcinoma (LELC) and EBV-associated gastric cancers (EBVaGC) are the most commonly associated. The role of EBV in the pathogenesis of NPC and in the modulation of its tumour immune microenvironment (TIME) has been increasingly well described. Much less is known about the pathogenesis and tumour-microenvironment interactions in other EBV-associated epithelial cancers. Despite the expression of EBV-related viral oncoproteins and an immune-inflamed cancer subtype, EBV-associated epithelial cancers have limited therapeutic options beyond conventional chemotherapy. Immune checkpoint inhibitors are effective only in a minority of these patients. Here, we examine the key similarities and differences of NPC, LELC, and EBVaGC and comprehensively describe the clinical, pathological and molecular characteristics of these cancers. A deeper comparative understanding of these EBV-driven cancers will potentially uncover targets in the tumour, TIME and stroma which may guide future drug development and cast light on resistance pathways to immunotherapy.